2002
DOI: 10.2463/mrms.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal Masses Caused by Pelvic Inflammatory Disease: MR Appearance

Abstract: MR imaging findings well reflect the basic pathological process of inflammation, and inflammatory adnexal masses are associated with relatively specific appearances in MR images. MR imaging can be a problem-solving alternative in the diagnosis of inflammatory adnexal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The present study found that only a proportion of TOAs present with typical MRI findings, while the majority showed mixed cystic and solid mass. TOAs with obvious solid component mostly presented striking rim-enhancement on post-contrast images, pathologically proven to be the abundant granulation tissue and fibrous tissue hyperplasia peripherally [ 21 ]. Moreover, the signal intensities in abscess cavity varied from low signal intensity to intermediate or high signal intensity on T1/T2-weighted images with 82.4% of TOAs showing similar signal intensity to those of soft-tissue or mucinous components of adnexal masses.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that only a proportion of TOAs present with typical MRI findings, while the majority showed mixed cystic and solid mass. TOAs with obvious solid component mostly presented striking rim-enhancement on post-contrast images, pathologically proven to be the abundant granulation tissue and fibrous tissue hyperplasia peripherally [ 21 ]. Moreover, the signal intensities in abscess cavity varied from low signal intensity to intermediate or high signal intensity on T1/T2-weighted images with 82.4% of TOAs showing similar signal intensity to those of soft-tissue or mucinous components of adnexal masses.…”
Section: Discussionmentioning
confidence: 99%
“…The signal intensity of the abscess content depends on its viscosity and protein content [18][19][20]. Tukeva et al [12] showed the superior sensitivity and specificity of MRI for TOA of 100% and 90% respectively, compared with transvaginal ultrasound (sensitivity of 56% and specificity of 86%).…”
Section: Discussionmentioning
confidence: 99%
“…With disease progression, TOAs show enhancing solid tissue, wall or septal thickening, and even papillary projections due to the formation of abundant granulation tissue and fibrous tissue hyperplasia [ 4 , 30 ]. It is known that tissue cellularity, interstitial oedema, and the fibrous component can influence the diffusion signal and ADC values [ 31 ].…”
Section: Discussionmentioning
confidence: 99%